Pengaruh Kedisiplinan Terhadap Kebiasaan Belajar Untuk Meningkatkan Hasil Belajar Siswa Kelas XII SMA Negeri 2 Tondano - Jelita Nainggolan; Orbanus Naharia; Meity Tanor (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study seeks to ascertain the extent of student discipline in relation to their study habits and examine its impact on enhancing student academic performance. The research methodology employs a correlational design to ascertain the correlation between discipline and study habits in order to enhance the academic performance of class XII students at SMA Negeri 2 Tondano. The population consisted of 46 pupils, and the sample was obtained by a random sampling procedure or by random selection. Random sampling is a technique for selecting samples in a random manner, ensuring that every member of the population has an equal chance of being chosen. The sample size in this study comprised 30 students. The findings of the research, which employed descriptive statistical analysis, indicate that the mean student discipline score is 33.13, the student study habits score is 30.43, and the mean student learning score is 90.6. The research findings, obtained through the use of Pearson product-moment correlation, indicate that the value of rcount is greater than rtable for a sample size of 30, specifically 0.394. If rcount > rtable, it indicates that discipline has an impact on the study habits and learning outcomes of class XII students at SMA Negeri 2 Tondano. If the count of r (rcount) is greater than the count of r in the table (rtable), the null hypothesis (HO) is rejected and the alternative hypothesis (H1) is accepted, according to the proposed research hypothesis. Discipline exerts a substantial impact on the study habits and academic achievements of twelfth-grade students at SMA Negeri 2 Tondano.